2010
DOI: 10.1371/journal.pone.0009643
|View full text |Cite
|
Sign up to set email alerts
|

Decreased NK Cell FcRγ in HIV-1 Infected Individuals Receiving Combination Antiretroviral Therapy: a Cross Sectional Study

Abstract: BackgroundFcRγ is an immunoreceptor tyrosine-based activation motif (ITAM)-signalling protein essential for immunoreceptor signaling and monocyte, macrophage and NK cell function. Previous study from our laboratory showed that FcRγ is down-regulated in HIV-infected macrophages in vitro. FcRγ expression in immune cells present in HIV-infected individuals is unknown.Methodology/Principal FindingsWe compared FcRγ expression in peripheral blood mononuclear cells isolated from HIV-1-infected individuals receiving c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
1
13
1
1
Order By: Relevance
“…However, the reported NK cell exhaustion and dysfunction in HIV-infected subjects (38)(39)(40)(41), which only partially normalize after ART, may reduce the effectiveness of Abs with Fc-mediated functions. Further investigation into the Fc␥RIIIa surface expression on autologous NK cells and the TIV-induced autologous NK cell activation in HIV-infected subjects is warranted to help us better understand the effect of HIV infection on NK cell-mediated ADCC after influenza vaccination.…”
Section: Discussionmentioning
confidence: 98%
“…However, the reported NK cell exhaustion and dysfunction in HIV-infected subjects (38)(39)(40)(41), which only partially normalize after ART, may reduce the effectiveness of Abs with Fc-mediated functions. Further investigation into the Fc␥RIIIa surface expression on autologous NK cells and the TIV-induced autologous NK cell activation in HIV-infected subjects is warranted to help us better understand the effect of HIV infection on NK cell-mediated ADCC after influenza vaccination.…”
Section: Discussionmentioning
confidence: 98%
“…65,67 NK cells from treated HIV-infected patients have reduced expression of key signaling proteins that are required for antibody-dependent cellular cytotoxicity; however, the factors causing this phenomenon are unknown. 68 Moreover, virologically suppressed HIV patients show activation of NK cells and persistent innate immune activation. 69 It remains to elucidate if NK cells from elderly people exhibit a similar activation pattern.…”
Section: Gradual Loss Of the Cd56mentioning
confidence: 99%
“…We have previously shown that expression of FcRg in NK cells is decreased in HIV-infected individuals receiving cART compared with HIV-uninfected controls (12). We hypothesized that HIVassociated immune activation causes downregulation of FcRg in NK cells, leading to inhibition of ADCC signaling.…”
mentioning
confidence: 97%
“…We have previously reported changes in NK cells purified from HIV patients receiving cART, where expression of key signaling proteins required for Ab-dependent cellular cytotoxicity (ADCC) was substantially reduced (12). NK cells in peripheral blood are commonly defined as belonging to one of two subsets.…”
mentioning
confidence: 99%